Recovery priorities in degenerative cervical myelopathy: a cross-sectional survey of an international, online community of patients. Issue 10 (10th October 2019) - Davies, Benjamin; Mowforth, Oliver; Sadler, Iwan; Aarabi, Bizhan; Kwon, Brian; Kurpad, Shekar; Harrop, James S; Wilson, Jefferson R; Grossman, Robert; Fehlings, Michael G; Kotter, Mark
Abstract : Objectives: To establish the recovery priorities of individuals suffering with degenerative cervical myelopathy (DCM). Design: A cross-sectional, observational study. Setting: Patients from across the world with a diagnosis of DCM accessed the survey over an 18-month period on Myelopathy.org, an international myelopathy charity. Participants: 481 individuals suffering from DCM completed the online survey fully. Main outcome measures: Functional recovery domains were established through qualitative interviews and a consensus process. Individuals were asked about their disease characteristics, including limb pain (Visual Analogue Scale) and functional disability (patient-derived version of the modified Japanese Orthopaedic Association score). Individuals ranked recovery domains (arm and hand function, walking, upper body/trunk function, sexual function, elimination of pain, sensation and bladder/bowel function) in order of priority. Priorities were analysed as the modal first priority and mean ranking. The influence of demographics on selection was analysed, with significance p <0.05. Results: Of 659 survey responses obtained, 481 were complete. Overall, pain was the most popular recovery priority (39.9%) of respondents, followed by walking (20.2%), sensation (11.9%) and arm and hand function (11.5%). Sexual function (5.7%), bladder and bowel (3.7%) and trunk function (3.5%) were chosen less frequently. When considering the average ranking of symptoms, while pain remained the priority (2.6±2.0), this was closely followed by walking (2.9±1.7) and arm/hand function (3.0±1.4). Sensation ranked lower (4.3±2.1). With respect to disease characteristics, overall pain remained the recovery priority, with the exception of patients with greater walking impairment ( p <0.005) who prioritised walking, even among patients with lower pain scores. Conclusions: This is the first study investigating patient priorities in DCM. The patient priorities reported provide an important framework for future research and will help to ensure that it is aligned with patient needs.